Development Of A Mission-X Game-Oriented Number Head Together Learning Type To Improve Students' Social Skills In Elementary School - Suwadi, Sunarti; Arismunandar; Kamaruddin Hasan (Cita konsultindo, 2025)
ABSTRACT Social skills are an important part of learners' lives in order to interact with their environment. so this needs to be taught and trained to children from an early age. The social skills of students today are felt by educators to be weak, which causes them to have difficulty in interacting with their surroundings, so that students become inferior. Less interesting and rigid learning in the classroom makes learning social skills very difficult to implement, resulting in low social skills of students. This development research aims to describe the needs analysis of developing the NHT-MX learning type to improve students' social skills in elementary schools; (ii) Know the description of the NHT-MX learning type for students in elementary schools; (iii) Know the level of validity and practicality of the NHT-MX learning type for students in elementary schools; (iv) Know the level of practicality of the NHT-MX learning type for students in elementary schools; (v) Know the effectiveness of the NHT-MX learning type to improve students' social skills in elementary schools. This research is a development research with validation, observation, and questionnaire data collection techniques. The results showed that (i) The Number Head Together learning type model oriented to the Mission-X game (NHT-MX) was declared